A two-stage MPPT controller for PV system based on the improved artificial bee colony and simultaneous heat transfer search algorithm. (January 2023) - Gong, Linjuan; Hou, Guolian; Huang, Congzhi
Abstract: The maximum power point tracking (MPPT) controller can monitor the voltage and current of photovoltaic (PV) array in real-time to acquire the maximum power output for battery charging in PV system. In order to improve the accuracy and rapidity of tracking process, a bionic two-stage MPPT control strategy composed of fast positioning stage and precise determination stage is proposed in this paper for optimizing the duty cycle d of DC–DC converter. Firstly, an improved artificial bee colony algorithm with simplified probability selection mechanism and novel employed bee phase is presented to balances exploration and exploitation for excellent rapidity in positioning rough search region around global peak. Then, the simultaneous heat transfer search (SHTS) algorithm is adopted for accurately acquiring the global maximum power point in obtained search region. On the one hand, the SHTS can reduce the subjectivity in artificial setting of the parameters to ensure the universality and accuracy of search process. On the other hand, the parallel search in SHTS can decrease the optimization time effectively. Finally, extensive simulation results illustrate that this two-stage MPPT strategy shows excellent performance in precisely identifying the GMPP of PV system with phenomenal rapidity among multiple peaks. Moreover, it outperforms all the counterparts in tracking speed and accuracy under partial shading conditions. Highlights: A two-stage MPPT controller is designed considering tracking speed and accuracy. An improved artificial bee colony algorithm is adopted in the early stage of MPPT. The simultaneous heat transfer search algorithm is used in the later stage of MPPT. The proposed MPPT scheme is applied to PV system under various shading conditions.